2003
DOI: 10.1148/radiol.2272020311
|View full text |Cite
|
Sign up to set email alerts
|

Perirolandic Cortex of the Normal Brain: Low Signal Intensity on Turbo FLAIR MR Images

Abstract: On turbo FLAIR images the PRC generally has a low SI in the neurologically normal brain, and this helps as an additional landmark in identifying the sensorimotor cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Ex vivo experiments with fixated brain tissue have shown that the hyperintense signal does not originate from the arachnoid and that it is absent if the cortex is partly removed (19). A similar superficial hyperintensity was described in previous double inversion-recovery and turbo FLAIR studies (11,13). With inversion pulses that efficiently null the signal of the cerebrospinal fluid, this hyperintense signal of the adjacent superficial cortex becomes obvious, especially with high-resolution imaging methods with high SNR.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Ex vivo experiments with fixated brain tissue have shown that the hyperintense signal does not originate from the arachnoid and that it is absent if the cortex is partly removed (19). A similar superficial hyperintensity was described in previous double inversion-recovery and turbo FLAIR studies (11,13). With inversion pulses that efficiently null the signal of the cerebrospinal fluid, this hyperintense signal of the adjacent superficial cortex becomes obvious, especially with high-resolution imaging methods with high SNR.…”
Section: Discussionsupporting
confidence: 75%
“…The most important finding in the current study was a multiple-layer appearance of the cerebral cortex in all investigated brain regions at high-resolution 3D FLAIR MR imaging at 7.0 T. Previously, at 1.5-T MR imaging, hypointensities in the perirolandic cortex were observed, but they were not observed elsewhere around the cerebral cortex (11). Similarly, a triple-layer appearance of BA 4 has been described with a thin-section double inversion-recovery MR imaging region (variance, 0.08 6 0.02), anterior frontal region (variance, 0.10 6 0.02), and occipital region (variance, 0.11 6 0.02).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…To define precisely the region of the PMC with the help of its characteristic features, special MR sequences have been used in vivo and in vitro at various field strengths up to 9.4 T [2,4,6,10,12,14,[19][20][21][22]. Instead of complex examinations, we have tried to localise the PMC in a simple way by using DWI, which is performed during routine MRI.…”
Section: Discussionmentioning
confidence: 99%
“…T2 shortening of the primary motor cortex (PMC) has been demonstrated both in normal adults and in patients with various neurodegenerative diseases [1][2][3][4][5]. Although the detection of T2 hypointensity depends on the field strength and the applied sequences, it has been demonstrated that T2 hypointensity is a constant finding in normal adults at 3 T using susceptibility-weighted imaging [6].…”
Section: Introductionmentioning
confidence: 99%